2020
DOI: 10.1016/j.matchemphys.2020.122870
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Cs2Pb1-xBixCl2I2 (0 ≤ x ≤ 0.15) derivative perovskite

Abstract: Synthesis and characterization of Cs2Pb1-xBixCl2I2 (0 ≤ x ≤ 0.15) derivative perovskite. (2020) Materials Chemistry and Physics, 247. 122870.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…Color of the compounds evolves from bright yellow to dark orange, via the continuous increase of Pb elements in the structure, which indicates that lead is possibly getting incorporated into the structure. A similar kind of change in color of the compound is observed when Bi is doped in APbBr 3 (A = MA and Cs) perovskites. ,, …”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Color of the compounds evolves from bright yellow to dark orange, via the continuous increase of Pb elements in the structure, which indicates that lead is possibly getting incorporated into the structure. A similar kind of change in color of the compound is observed when Bi is doped in APbBr 3 (A = MA and Cs) perovskites. ,, …”
Section: Resultssupporting
confidence: 53%
“…A similar kind of change in color of the compound is observed when Bi is doped in APbBr 3 (A = MA and Cs) perovskites. 33,39,40 The compositional study of various lead substituted-layered perovskites is performed using inductively coupled plasma atomic emission spectroscopy (ICP−AES). The Bi to Pb atomic concentrations obtained in ICP−AES analysis are 105.31, 39.85, 19.81, 11.84, and 5.9 for Pb:5, Pb:10, Pb:15, Pb:20, and Pb:25, respectively (as listed in Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This inorganic 2D phase of Ruddlesden‐Popper structural type is stable in air and at high temperature (T∼400 °C), with a higher band gap (E g ∼3.0 eV) and shows photoconductivity. During our research investigations on the doping and use of the 2D Cs 2 PbCl 2 I 2 phase, we have recently noticed that mixing a 2D inorganic material with a 3D inorganic perovskite could keep the black phase for longer than usual after heating [22] . This observation was confirmed by Li.…”
Section: Introductionmentioning
confidence: 73%
“…The peak shape analysis can sometimes give valuable information about the crystallite size and micro‐strains, using the Williamson‐Hall method, for instance. Indeed, strain engineering operated in several works showed that there is a tendency to improve the stability while reducing strain, or more precisely applying compressive strain to perovskite films [13,22,30,42–45] . Such parameter analysis could actually shed a light on the differences observed on perovskite materials in the powder and thin film states.…”
Section: Resultsmentioning
confidence: 99%
“…An injection of oleylamine halide into oleic acid has also allowed to obtain manganese-doped Cs 2 PbCl 2 I 2 nanoplatelets that show an increased photoluminescence and a quantum yield of 16% [27]. The introduction of a doping agent in the structure seems to be a good strategy in order to enhance photoluminescence activity, conductivity and to modify the microstructure, as shown in our recent work performed on powder samples of the bismuth-doped Cs 2 PbCl 2 I 2 phase [28]. In another work, we have also showed that the addition of such 2D phase prepared in solution to a 3D all-inorganic perovskite-based halide thin layer can stabilize the black form of the perovskite which is of strong interest for photovoltaics [29].…”
Section: Synthesis Of 2d Single Crystals At Room Temperaturementioning
confidence: 86%